Pengaruh Determinan Tidak Langsung Stunting dengan Kejadian Stunting Balita di Papua New Guinea Tahun 2018: Indirect Determinant Effects of Stunting with Toddler Stunting Incident in Papua New Guinea in 2018 - Khoiriyah, Riza; Mahmudiono, Trias; Nadhiroh, Siti Rahayu (Amerta Nutrition, 2024)
Background: Papua New Guinea has a significant problem with stunting, with a prevalence rate of 46.5% in 2018. Objectives: This study aimed to analyze the effect of various factors on stunting in Papua New Guinea in 2018. These factors include characteristics of the child (gender, age, and ownership of health insurance) and household environmental factors such as the mother's education level, number of toddlers in the household, drinking water sources, and availability of restrooms. Methods: This study employed a cross-sectional research design using secondary data from "The Demographic and Health Surveys (DHS) in Papua New Guinea in 2018." The variables of interest were extracted and subjected to data cleaning procedures, resulting in a final sample size of 744 toddler data points available for analysis. The chi-square test and logistic regression were employed for statistical analysis. Results: The study revealed that mothers of toddlers who had never received any formal education were more likely to have toddlers who experienced stunting. The statistical analysis showed a significant association between the lack of maternal education and toddler stunting (p-value=0.012; odds ratio=1.488; 95% confidence interval [1.092; 2.028]). Additionally, toddlers in the age group of 24-59 months were found to be at a higher risk of experiencing stunting. The statistical analysis indicated a strong association between this age group and toddler stunting (p-value<0.001; odds ratio=1.770; 95% confidence interval [1.301; 2.408]). Conclusions: The approach to addressing stunting in toddlers aged 24-59 months emphasizes the implementation of targeted and responsive interventions, with particular emphasis on the significance of investing in the education of toddler mothers in Papua New Guinea. However, in terms of prevention, it is crucial to administer the intervention before the toddler reaches the age of 24-59 months, as stunting is a visible result of long-term malnutrition.